All-Textile Broadband Circularly-Polarized 2 × 2 Array Antenna Based on Metasurface - Tu Tuan Le; Yong-Deok Kim; Tae-Yeoul Yun (IEEE Access, 2024)
This paper presents the design and analysis of an all-textile broadband circularly polarized array antenna based on metasurface (MTS), which offers a promising solution for developing a high-performance, lightweight, and comfortable antenna for various wearable applications. The array antenna configuration comprises $2×2$ MTS elements, a ground plane, and a sequential feeding network. The MTS radiator of the antenna element is first designed and miniaturized by implementing diagonal slits. It is fed from a $50~Ω $ microstrip line through different-length cross-slot etched in the center of the ground plane, which has a narrow axial ratio bandwidth (ARBW). To enhance the antenna performances, the MTS array antenna is formed into a $2×2$ arrangement. Its radiators are fed by a 90° phase difference sequential series-feeding network. The measured impedance bandwidth (IBW) of 72% on the human body is achieved, and the measured ARBW of 47.9% on a phantom head is achieved. High broadside gain and moderate radiation efficiency are observed within the ARBW. Simulated specific absorption rates (SARs) under US and European standards are below the safe level. The simulated and measured results show very good agreement.